APLIKASI JAMUR PEMUTIH PADA AMPAS TEBU SEBAAI BAHAN BAKU KERTAS - Zulferiyenni, Zulferiyenni; Hidayati, Sri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
Usage of high chemicals at process of paper and pulp generate much negative impact at environment. To lessen the mentioned used by enzyme of mushroom upon which white rot fungi because owning ability of lignin degradation selectively and only elaborating and cellulose of hemicelluloses in number a few. Result of research indicate that from is fourth of isolate test that is ampas tebu busuk isolate, isolate P. Porigens, isolate V. Volvaceae , Ganoderma sp and Omphilia sp can existing lignin degradable in bags and yield enzyme of laccase. Omphilia sp have potency for the degradable of lignin equal to 72% with degradation of cellulose equal to 0, 5% and yield enzyme activity of laccase equal to 37, 56 units / ml. Â Keyword:Â bagasse, lignocellulose, biopulping